1977
DOI: 10.3102/00028312014003263
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Model for Determining Whether the Treatment is Actually Implemented

Abstract: Determining whether or not the treatment or innovation under study is actually in use, and if so, how it is being used, is essential to the interpretation of any study. The concept of Levels of Use of the Innovation (Loll) permits an operational, cost-feasible description and documentation of whether or not an innovation or treatment is being implemented. Data from change research and evaluation studies indicate that there are eight different LoU's that can be reliably measured. Knowing the LoU of individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
8

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(86 citation statements)
references
References 5 publications
5
73
0
8
Order By: Relevance
“…Plusieurs auteurs ont discuté des activités nécessaires à la réalisation d'une telle mesure (Hall et Loucks, 1977 ;Leithwood et Montgomery, 1980 ;Yin, 1982 ;Scheirer et Rezmovic, 1983 ;Rezmovic, 1984 ;Breeke, 1987 ;Scheirer, 1987). Cette composante de l'analyse de l'implantation vise à documenter et à suivre le niveau d'opérationnalisation d'une intervention (Patton, 1986 ;Veney et Kaluzny, 1985 ;Rossi et Freeman, 1985).…”
Section: Questions De Recherche Stratégie D'évaluation Et Devisunclassified
“…Plusieurs auteurs ont discuté des activités nécessaires à la réalisation d'une telle mesure (Hall et Loucks, 1977 ;Leithwood et Montgomery, 1980 ;Yin, 1982 ;Scheirer et Rezmovic, 1983 ;Rezmovic, 1984 ;Breeke, 1987 ;Scheirer, 1987). Cette composante de l'analyse de l'implantation vise à documenter et à suivre le niveau d'opérationnalisation d'une intervention (Patton, 1986 ;Veney et Kaluzny, 1985 ;Rossi et Freeman, 1985).…”
Section: Questions De Recherche Stratégie D'évaluation Et Devisunclassified
“…The simple but powerful phrase "change is a process, not an event" connotes that something is happening over a period of time to transform individuals and situations (Hall & Loucks 1977). Furthermore, the focus on teambuilding has been embedded in all of the discussions on co-teaching.…”
Section: Post Launchmentioning
confidence: 99%
“…They illustrate the changes in behavior that individuals show when they are shifting through their adoption of the innovation (Al Aghbari, 2007), and show a continuum of growth gradually moving from not using the innovation towards using different skills, experiences, and looking for various ways to modify the existing innovation (Berg, 1993, cited in Mustafa, 2010. They, as summarized by Hall and Loucks (1977), permit an operational, cost-feasible explanation and certification of whether or not an innovation or treatment is being adopted. They added that data from research of change and evaluation studies showed that the LoU could be reliably measured.…”
Section: The Levels Of Usementioning
confidence: 99%
“…The LoU, as stated by Hall and Loucks (1977), illustrate the users and the nonusers of an innovation. They illustrate the changes in behavior that individuals show when they are shifting through their adoption of the innovation (Al Aghbari, 2007), and show a continuum of growth gradually moving from not using the innovation towards using different skills, experiences, and looking for various ways to modify the existing innovation (Berg, 1993, cited in Mustafa, 2010.…”
Section: The Levels Of Usementioning
confidence: 99%
See 1 more Smart Citation